Gut epithelial cell-derived exosomes trigger posttrauma immune dysfunction. Issue 2 (February 2018) - Kojima, Mitsuaki; Costantini, Todd W.; Eliceiri, Brian P.; Chan, Theresa W.; Baird, Andrew; Coimbra, Raul
Abstract : BACKGROUND: Exosomes are extracellular vesicles that act as endogenous mediators of the immune response. We have previously shown that exosomes released into mesenteric lymph (ML) following trauma (T)/hemorrhagic shock (HS) induce proinflammatory cytokine production in macrophages and are involved in the pathogenesis of postshock acute lung injury. However, the cellular origin of ML exosomes and their role in the posttrauma immune response remains unclear. We hypothesized that exosomes released from damaged-intestinal epithelial cells contribute to posttrauma immune dysfunction by altering the function of dendritic cells (DCs), key regulators of the adaptive immunity. METHODS: Male rats underwent cannulation of the femoral artery, jugular vein and ML duct. T/HS was induced by laparotomy and 60 minutes of hemorrhagic shock followed by resuscitation. The ML was collected before (preshock) and after T/HS (post-T/HS) for isolation of exosomes. Surface epitopes of exosomes isolated from ML were assessed by flow cytometry to determine their cellular origin and phenotypic changes. The immunomodulatory effects of ML exosomes on DCs were assessed by Annexin V apoptosis assay, expression of costimulatory molecules, and antigen-presenting capacity to lymphocytes. RESULTS: Exosomes isolated from ML highly expressed CD63 (exosome marker) and epithelial cell-specific marker, suggesting their derivation from intestinal epithelial cells. The expression of immunomodulatory molecules, such as major histocompatibility complex class II and Fas ligand on ML exosomes, was significantly increased after T/HS. Coincubation of DCs with exosomes isolated from ML after T/HS increased DC apoptosis twofold compared with preshock ML exosomes. Furthermore, post-T/HS ML exosomes significantly suppressed lipopolysaccharide-mediated expression of CD80 and CD86 on DCs as well as decreased their antigen-presenting capacity to induce lymphocytes proliferation. CONCLUSION: Gut epithelial cells release immunomodulatory exosomes into the ML after T/HS and resuscitation. Mesenteric lymph exosomes may be critical mediators of posttraumatic immunosuppression causing depletion and dysfunction of DCs.